Psychometric properties of a digital citizenship questionnaire - Nordin, Mohamad Sahari; Tunku Ahmad, Tunku Badariah; Zubairi, Ainol Madziah; Ismail, Nik Ahmad Hisham; Abdul Rahman, Abdul Hamid; Trayek, Fuad; Ibrahim, Mohd Burhan (Canadian Center of Science and Education, 2016)
The purpose of this study was twofold, i.e. to examine the extent to which students’ self-reported use of digital technology constituted meaningful and interpretable dimensions of the digital citizenship construct, and to test the adequacy of the construct in terms of its reliability, convergent validity, discriminant validity, and measurement equivalence for male and female students. The sample consisted of 391 undergraduates from 15 institutions of higher education in Malaysia. The data were collected using a self-reported 17-item questionnaire measuring university students’ digital citizenship behaviours. The results of the study supported and extended the results of previous work on students’ behaviors when using digital technology. The study found evidence that students’ digital citizenship is a valid and reliable multidimensional construct, and the measurement is gender-invariant. The findings are useful in making evidence-informed decisions in choosing and developing instructional interventions to produce ethical and responsible technology users, and in informing future research in the area.